Improving Students’ Speaking Skills by Using Storytelling - Caroline Sabatiana Ambarita; Junita Siahaan; Resperdiana Purba; Irma Khoirot Daulay (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe the improvement of speaking skills using the story telling method in X MIPA-1 SMAS Yayasan Pendidikan Pangeran Antasari. The research method used is qualitative. Two sessions were held to perform this research. The initial study’s findings revealed that during the first meeting, 50% of the participants dared to speak English in front of the class and 60% were able to do so. At the second meeting, 80% of the students were willing to speak in front of the class and could speak English to 90% level. From the data obtained, it can be concluded that there was an increase in speaking ability for X MIPA-1 SMAS Yayasan Pendidikan Pangeran Antasari. Key words: Story Telling, Teaching Speaking Skills